Pengaruh Citra Merek, Harga, dan Kualitas Produk terhadap Loyalitas Melalui Kepuasan Konsumen sebagai Variabel Intervening - Difta Octavia Saridewi; Rusdi Hidayat Nugroho (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to determine: (1) the effect of brand image on customer loyalty through customer satisfaction, (2) the effect of price on customer loyalty through customer satisfaction, (3) the effect of product quality on customer loyalty through customer satisfaction, (4) the effect of brand image on customer loyalty, (5) The effect of price on customer loyalty, (6) The effect of product quality on customer loyalty, and (7) The effect of consumer satisfaction on customer loyalty. This research method uses quantitative methods. The population in this study are all consumers who buy and consume Bear Brand Milk products in the city of Surabaya. While the sample in this study were consumers who consumed Bear Brand Milk products more than once in the city of Surabaya with an age range of 15 - 54 years with a sample of 100 people. The data analysis technique used is Path analysis. With the results of the study that the brand image variable (X1) has a positive and significant effect on customer loyalty (Y) through customer satisfaction (Z). Price variable (X2) has a positive and significant effect on customer loyalty (Y) through customer satisfaction (Z). Product quality variable (X3) has a positive and significant effect on customer loyalty (Y) through customer satisfaction (Z). Brand image variable (X1) has a positive and significant effect on customer loyalty (Y). Price variable (X2) has no positive and insignificant effect on customer loyalty (Y). Product quality variable (X3) has a positive and significant effect on customer loyalty (Y). Keywords: Brand image, price, product quality, consumer satisfaction, customer loyalty